ChemInform Abstract: Highly Convergent Synthesis of Intensively Blue Emissive Furo[2, 3‐c]isoquinolines by a Palladium‐Catalyzed Cyclization Cascade of Unsaturated Ugi Products. Issue 27 (16th June 2016) - Moni, Lisa; Gers‐Panther, Charlotte F.; Anselmo, Manuel; Mueller, Thomas J. J.; Riva, Renata
Abstract: An approach to the unusual furo[2, 3‐c]isoquinoline scaffold is presented.